REDUCE THE INTENSITY OF LABOR PAIN WITH AQUPRESSURE - Solihah, Eneng; Sugiarsih, Ugi (Universitas Pendidikan Indonesia (UPI), 2022)
Project-based learning is one of the lessons that is able to direct participants. The process of childbirth is identical to the feeling of pain as a manifestation of the birth process which begins with uterine contractions, cervical dilatation and effacement. It is a physiological process, as a subjective experience of the physical sensations associated with the stages of labour. To reduce the sensation of labor pain, it is necessary to have pain management in labor using non-pharmacological methods, one of which is acupressure. The purpose of this study was to determine the effect of acupressure on the level of labor pain. Methods: The research design in this study was a pre-experiment with a one-group pre-post test design. The population of all women giving birth normally with a sample of 52 respondents for the intervention group and 52 respondents for the control group. The sampling technique was accidental sampling. Bivariate analysis using the Wilcoxon test. Results: Statistical tests using the Wilcoson test obtained p value = 0.000 (p value 0.05) meaning that acupressure has been proven to significantly reduce the intensity of labor pain. Conclusion: acupressure can reduce the intensity of physiological labor pain in primigravidas in labor during the first active phase.